Glycoside hydrolases from extremophiles isolated in Iceland. alpha-L-Rhamnosidases and pectin degrading enzymes - Birgisson, Hakon (Department of Biotechnology, Lund University, 2004)
Extreme environments (high and low temperature, high and low pH, etc.) are inhabited by a vast and diverse flora of microorganisms, which are adapted to these environments (extremophiles). The enzymes produced by extremophiles are active under these harsh conditions and are thus applicable in processes, where conditions are outside the working range of enzymes originating from mesophiles. In this thesis, both cold-adapted and heat-adapted glycoside hydrolases identified in microorganisms isolated in cold and hot environments in Iceland are described. Screening of soil samples for pectinolytic microorganisms, resulted in isolation of four cold-adapted yeast species, which all excreted one or more polygalacturonases. Analysis of the 5.8S rDNA and the 26S rDNA D1/D2 domain, revealed that the yeasts were most closely related to Cystofilobasidium capitatum, Cystofilobasidium lari-marini, Cryptococcus macerans and Cryptococcus aquaticus. Examination of the polygalacturonase activities revealed that at 2 °C, all samples showed 8-18% activity of their activities at optimal temperatures. Screening of a sequenced genome of a novel thermophilic bacterium resulted in isolation, cloning and expression of three genes. Two of the genes encoded for alpha-L-rhamnosidases and one for alpha-L-arabinofuranosidase. All purified recombinant products were found to have broad pH activity curves, temperature optima at 70 °C and relatively high thermostability. One of the recombinant alpha-L-rhamnosidases was produced with a His tag, to facilitate purification of large quantities of the enzyme. The purified enzyme was subsequently used for crystallization. Two crystal forms were obtained. X-ray analysis indicated that one of the crystal forms may be useful for structural determination of the enzyme. Finally, the recombinant cells producing one of the two recombinant alpha-L-rhamnosidases were immobilized in alginate beads, which were used for construction of a bioreactor for production of L-rhamnose from a natural substrate at elevated ...